2022
DOI: 10.1128/spectrum.02056-21
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Agent 3,3'-Diindolylmethane Inhibits Multispecies Biofilm Formation by Acne-Causing Bacteria and Candida albicans

Abstract: Since indoles are widespread in nature (even in human skin), we hypothesized that indole and its derivatives might control biofilm formation of acne-causing bacteria ( Cutibacterium acnes and Staphylococcus aureus ) and fungal Candida albicans . The present study reports for the first time the antibiofilm and antimicrobial activities of several indoles on C. acnes .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…Although DIM has been shown to effectively limit larval settlement, providing an antifoulant effect in the marine environment [ 91 ], to the best of our knowledge, our study is the first to show the anti-biofilm activity and virulence attenuation of the agent against Gram-negative bacteria. Moreover, a recent study showed that DIM has antibiofilm activity on Candida albicans and acne-causing bacteria [ 92 ]. Based on its anti-biofilm properties, which affect diverse strains of bacteria, the results of this study suggest that DIM is potentially suitable for attenuating a wide range of bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Although DIM has been shown to effectively limit larval settlement, providing an antifoulant effect in the marine environment [ 91 ], to the best of our knowledge, our study is the first to show the anti-biofilm activity and virulence attenuation of the agent against Gram-negative bacteria. Moreover, a recent study showed that DIM has antibiofilm activity on Candida albicans and acne-causing bacteria [ 92 ]. Based on its anti-biofilm properties, which affect diverse strains of bacteria, the results of this study suggest that DIM is potentially suitable for attenuating a wide range of bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, alizarin also suppressed the expression of hyaluronate lyase ( hly ; a putative virulence factor), which is capable of destroying the epidermal extracellular matrix and might promote inflammation spread [ 2 ]. Interestingly, it was recently reported that 3,3′-diindolylmethane (an antibiofilm agent) downregulated the expressions of PPA1796, PPA2105, and hly in C. acnes [ 37 ]. Alizarin has also been reported to downregulate two adhesin and two invasion-related genes [ 1 ] and PPA1715 but not to affect the expressions of two other adhesins (PPA1983 and PPA1906) [ 38 ], which suggests that alizarin might inhibit the attachment to and the invasion of host tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Fungi and bacteria are the most common causes of UTI. A single species infection was generally treated with existing antimicrobials, but the polymicrobial cultures are recalcitrance to conventional treatments (Kim et al, 2022;Orazi & O'Toole, 2019;Raj et al, 2022). Therefore, we initially examined the inhibitory activity of BcN16E in killing the planktonic cells was analysed by fluorescence bioimaging.…”
Section: Discussionmentioning
confidence: 99%